Factors of the Extrinsic Pathway of Blood Coagulation in Tumour Associated Macrophages - Ádány, Róza; Kappelmayer, János; Berényi, Ernö; Szegedi, Andrea; Fábián, Erzsébet; Muszbek, László (Thrombosis and Haemostasis, 1989)
Despite the growing evidence implicating intratumoural fibrin formation in the progression of malignant tumours, the origin of coagulation factors that participate in extravascular clotting has not been elucidated. Using immunohistochemical methods we attempted to detect and localize clotting factors of extrinsic pathway in different human malignant tumours. Coagulation factors II, V, VII and X (FII, FV, FVII and FX) were detected in a huge number of cells showing spindle-shaped or stellate morphology. By double immunohistochemical labellings it was demonstrated that cells containing these clotting factors express monocyte/macrophage differentiation marker antigens recognized by Leu M3, Ki M7 and DAKO-macrophage monoclonal antibodies, i.e. they represent monocyte-derived, phagocytic tumour associated macrophages (TAMs). These findings suggest that TAMs can be viewed as clot cells, which in addition to the initiation of extravascular clotting by expressing procoagulant activity can also provide all the components necessary for the extrinsic thrombin formation.
Keywords: Macrophages; Intratumoural fibrin formation; Clotting factors